1971
DOI: 10.1128/iai.4.5.581-588.1971
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Phagocytosis by Interferon-Containing Preparations

Abstract: Exposure of mononuclear cells from the mouse peritoneal cavity to interferon (IF)-containing mouse sera enhanced phagocytosis of colloidal carbon particles by the cells. The same effect was observed when the cells were exposed to IF-containing cell culture harvest free of serum. The magnitude of this effect of IF-containing preparations paralleled the titer of IF and was not related to the dilution of various IF-containing serum specimens tested. The factor responsible for the enhancing effect was stable at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…Miorner et al, 1978 have shown that an immunostimulatory effect occurs at low interferon concentrations, comparable to those obtained in serum after interferon administration (Einhorn and Strander, 1978). Interferon may stimulate phagocytosis (Huang, et al, 1971) and change the antigenicity of interferon-treated cells (Lindahl, 1974;Killander et al, 1976).…”
Section: Discussionmentioning
confidence: 55%
“…Miorner et al, 1978 have shown that an immunostimulatory effect occurs at low interferon concentrations, comparable to those obtained in serum after interferon administration (Einhorn and Strander, 1978). Interferon may stimulate phagocytosis (Huang, et al, 1971) and change the antigenicity of interferon-treated cells (Lindahl, 1974;Killander et al, 1976).…”
Section: Discussionmentioning
confidence: 55%
“…Phagocytic activities of macrophages, monocytes, peritoneal cells and reticuloendothelial systems could be stimulated by interferon or its inducers to a significantly higher level. Huang et al (1971) demonstrated an increase of 200-300 per cent in phagocytic activity when mouse peritoneal macrophages were exposed to 50 units/ml of mouse interferon. They showed that this increase of activity could be achieved with several different preparations of mouse interferon and that the enhancing effect on macrophages could be eliminated by treatment with anti-mouse interferon antiserum (Donahoe and Huang, 1973).…”
Section: Enhancement Of Phagocytosismentioning
confidence: 96%
“…There are at least three possible mechanisms by which IFN plays a role in resistance to HSV infection (13) ; direct inhibition of the replication of HSV (19), augmentation of the lytic capacity of NK cells (4), and activation of macrophage function such as sequesteration of replicating HSV-1 (7) or lysis of virus-infected target cells (24). The reduction in the number of ICs produced by PECs of mice inoculated with +GC(LPV) when the animals were preinoculated with was presumed to reflect a complex combination of these three mechanisms.…”
Section: Discussionmentioning
confidence: 99%